(untitled) (The Journal of Academic Development, 2023)
This paper analyzes Nepalese individual investors’ consciousness and their investment on stocks. Investors’ consciousness creates positive environment for the investment which helps in capital formulation. This study has employed explorative research design to explain investors’ consciousness and investment on common stock in Nepalese stock market. Data were collected through survey from individual stock investors using structural questionnaire in Kathmandu valley in 2021. The estimated result of this study shows the level of investors’ consciousness (investors’ education and training, access to information, understanding of subjects and learning expectations etc.) is more than desirable level of 50 percent. Similarly, result indicates that conscious investors have chance of holding more common stock which indicates positive association between investors’ consciousness and level of investment in common stocks. Moreover, survey result reveals that investors assert problems on accessing of market information while making investment on stock in Nepalese stock market. This paper concludes that stock market should disseminate sufficient information of stocks, stock markets, stock returns, rules and regulation of security markets, security trading mechanism etc. to the investors through various training programs to make alert them for their sound investment decisions in Nepalese stock markets.